In vivo kinematics of healthy male knees during squat and golf swing using image-matching techniques - Murakami, Koji; Hamai, Satoshi; Okazaki, Ken; Ikebe, Satoru; Shimoto, Takeshi; Hara, Daisuke; Mizu-uchi, Hideki; Higaki, Hidehiko; Iwamoto, Yukihide (The knee, 2016)
Participation in specific activities requires complex ranges of knee movements and activity-dependent kinematics. The purpose of this study was to investigate dynamic knee kinematics during squat and golf swing using image-matching techniques. Five healthy males performed squats and golf swings under periodic X-ray images at 10 frames per second. We analyzed the in vivo three-dimensional kinematic parameters of subjects' knees, namely the tibiofemoral flexion angle, anteroposterior (AP) translation, and internal–external rotation, using serial X-ray images and computed tomography-derived, digitally reconstructed radiographs. During squat from 0° to 140° of flexion, the femur moved about 25mm posteriorly and rotated 19° externally relative to the tibia. Screw-home movement near extension, bicondylar rollback between 20° and 120° of flexion, and medial pivot motion at further flexion were observed. During golf swing, the leading and trailing knees (the left and right knees respectively in the right-handed golfer) showed approximately five millimeters and four millimeters of AP translation with 18° and 26° of axial rotation, respectively. A central pivot motion from set-up to top of the backswing, lateral pivot motion from top to ball impact, and medial pivot motion from impact to the end of follow-through were observed. The medial pivot motion was not always recognized during both activities, but a large range of axial rotation with bilateral condylar AP translations occurs during golf swing. This finding has important implications regarding the amount of acceptable AP translation and axial rotation at low flexion in replaced knees. IV •We analyzed knee kinematics of squat and golf swing using image-matching technique.•Squat exhibited screw-home movement, bicondylar rollback, and medial pivot motion.•Golf swing exhibited a large axial rotation with AP translation at low flexion.•These data implies acceptable AP translation and axial rotation in replaced knees.